Online health communities: how do community members build the trust required to adopt information and form close relationships?. Issue 1 (2nd January 2018) - Fan, Hanmei; Lederman, Reeva
Abstract: Online Health Communities (OHCs) have become a popular avenue for people to share common concerns about a health topic. However, because users of these forums tend not to have formal medical training, they often cannot verify objectively the soundness of the advice provided. Thus, there is a need to understand better the mechanism through which people trust and utilise information found on these forums. In testing a theory-based trust model, we find that forum users accept advice more readily as they develop cognitive trust (trust based on a cognitive assessment) and/or affective trust (trust based on an emotional connection). Affective trust is also closely related to formation of relational closeness. This indicates that, while both forms of trust are important, the development of emotional connections provides for long-term OHCs interactions. Findings here, indicate that prior exchanges are not needed to access and utilise OHC community resources. However, trust (developed through prior exchanges) is required for a recipient to leverage the contributor's social capital for information adoption and relational closeness. These findings allow the distribution of social capital to be viewed in terms of an asymmetrical model where it is possible to accept capital, in the form of advice, without first demonstrating trustworthiness. In the OHC setting the onus is on the contributor of advice to establish trustworthiness, whereas traditionally social capital theory requires receivers of capital to establish trust. These findings are important for site designers and provide insight to managers and developers of OHCs regarding the behaviours and motivations of forum users.